Transport Findings 2019
DOI: 10.32866/7766
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Reductions in Vehicle Kilometers Traveled from New Bicycle Facilities

Abstract: This paper presents a simple method for projecting the impact of new bicycle facilities on vehicle kilometers traveled. Our method starts with existing short-duration bicycle counts on or near the facility corridor, then applies six adjustment factors to project reductions in vehicle kilometers traveled. We examine the feasibility of measuring each factor and the range of their potential values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Current methods for estimating modal substitution factors at the project level frequently rely on intercept surveys of facility users following project construction ( 7 ). Because these surveys are applied retroactively, they have limited applicability in estimating modal substitution rates at the project planning stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current methods for estimating modal substitution factors at the project level frequently rely on intercept surveys of facility users following project construction ( 7 ). Because these surveys are applied retroactively, they have limited applicability in estimating modal substitution rates at the project planning stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One indication of the direction of the economic impact to local businesses of adding active travel facilities in the same area is the difference in spending habits of visitors based on the travel mode they use to get there. It is generally well established in the active travel literature that adding bicycle and pedestrian facilities to an area tends to increase cyclist and pedestrian use of that area (Volker, Handy, Kendall, & Barbour, 2019a, 2019b. That increased use should translate into increased spending at local businesses in the area if consumer spending remains the same among visitors who arrive by other travel modes (like driving and transit).…”
Section: Spending By Travel Modementioning
confidence: 99%
“…But there is evidence that active travel improvements like road diets (Gudz, Fang, & Handy, 2016;Huang, Stewart, & Zegeer, 2002) and complete streets retrofits (Shu, Quiros, Wang, & Zhu, 2014) can increase bicycling or pedestrian volumes while having little to no effect on vehicular traffic flow. In addition, a recent review of the literature on changes in bicycle ridership following installation of a new bicycle facility concluded that "sizeable percentage increases in ridership can be expected along the routes of new Class I, Class II, and Class IV facilities" (Volker et al, 2019a, p. 20;Volker & Handy, 2019).…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…This is similarly reflected in the usage patterns of corridors that receive such treatments, implying that well designed interventions can increase bicycle mode share (Boss et al, 2018; Parker et al, 2013; Schoner and Levinson, 2014). A review of the literature on the impact of Class I, II, and IV bike infrastructure (exclusive bicycle ROW, designated on-street bicycle lanes, and protected on-street lanes, respectively) estimated that all three types of facilities often double ridership (Volker and Handy, 2019). The same study estimated that 10% of these new trips substituted automotive trips.…”
Section: Introductionmentioning
confidence: 99%